STK38 kinase acts as XPO1 gatekeeper regulating the nuclear export of autophagy proteins and other cargoes. (23rd September 2019) - Martin, Alexandre PJ; Jacquemyn, Maarten; Lipecka, Joanna; Chhuon, Cerina; Aushev, Vasily N; Meunier, Brigitte; Singh, Manish K; Carpi, Nicolas; Piel, Matthieu; Codogno, Patrice; Hergovich, Alexander; Parrini, Maria Carla; et al.
Abstract: STK38 (also known as NDR1) is a Hippo pathway serine/threonine protein kinase with multifarious functions in normal and cancer cells. Using a context‐dependent proximity‐labeling assay, we identify more than 250 partners of STK38 and find that STK38 modulates its partnership depending on the cellular context by increasing its association with cytoplasmic proteins upon nutrient starvation‐induced autophagy and with nuclear ones during ECM detachment. We show that STK38 shuttles between the nucleus and the cytoplasm and that its nuclear exit depends on both XPO1 (aka exportin‐1, CRM1) and STK38 kinase activity. We further uncover that STK38 modulates XPO1 export activity by phosphorylating XPO1 on serine 1055, thus regulating its own nuclear exit. We expand our model to other cellular contexts by discovering that XPO1 phosphorylation by STK38 regulates also the nuclear exit of Beclin1 and YAP1, key regulator of autophagy and transcriptional effector, respectively. Collectively, our results reveal STK38 as an activator of XPO1, behaving as a gatekeeper of nuclear export. These observations establish a novel mechanism of XPO1‐dependent cargo export regulation by phosphorylation of XPO1's C‐terminal auto‐inhibitory domain. Synopsis: Cytoplasmic accumulation of STK38 kinase is essential for starvation‐induced autophagy. STK38 phosphorylates and activates the nuclear export factor XPO1, thereby supporting the shuttling of the autophagy regulator Beclin1 and other XPO1 cargoes to the cytoplasm. XPO1 is a substrate for the STK38 kinase. XPO1 is activated by this phosphorylation event on Ser1055. STK38 behaves as a regulator of XPO1 activity, which is inactive in absence of phosphorylation of its Ser1055. Abstract : Cytoplasmic accumulation of STK38 kinase is essential for starvation‐induced autophagy. STK38 phosphorylates and activates the nuclear export factor XPO1, thereby supporting the shuttling of the autophagy regulator Beclin1 and other XPO1 cargoes to the cytoplasm.